Matching food with mouths: A statistical explanation to the abnormal decline of per capita food consumption in rural China - Xiaohua Yu; David Abler (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2015)
This study provides an alternative explanation for the unusual apparent decline in food consumption in rural China after 2000. We find that it is mainly attributable to significant measurement errors in the Chinese Rural Household Survey and the calculation of per capita food consumption. In a household survey, total consumption for a household in a certain period is often well recorded, and per capita consumption is obtained by dividing total consumption by household size. Such a calculation of per capita food consumption is vulnerable to a mismatch between food and mouths. Total consumption may be subject to measurement errors caused primarily by food away from home (FAFH). Also, the household size recorded in the survey is not necessarily the same as the number of mouths (consumption household size), who consume the food recorded in the survey. Our results indicate that food consumption in rural China is currently being underestimated by about 30%. Our results also indicate that income elasticities of food consumption are greater than measured elasticities based on the Rural Household Survey data.
Keywords: Q11; C81; O13; 330; food demand; underreporting; rural China; food away from home; off-farm migration